Aptamer Turn-On SERS/RRS/Fluorescence Tri-mode Platform for Ultra-trace Urea Determination Using Fe/N-Doped Carbon Dots - Li, Chongning; Li, Jiao; Liang, Aihui; Wen, Guiqing; Jiang, Zhiliang (Frontiers in Chemistry, 2021)
Sensitive and selective methods for the determination of urea in samples such as dairy products are important for quality control and health applications. Using ammonium ferric citrate as a precursor, Fe/N-codoped carbon dots (CDFeN) were prepared by a hydrothermal procedure and characterized in detail. CDFeN strongly catalyzes the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) by H2O2 to turn on an indicator molecular reaction, forming an oxidized tetramethylbenzidine (TMBox) probe with surface-enhanced Raman scattering, resonance Rayleigh scattering, and fluorescence (SERS, RRS, and FL) signals at 1598 cm-1, 370 nm, and 405 nm, respectively. The urea aptamer (Apt) can turn off the indicator reaction to reduce the tri-signals, and the addition of urea turns on the indicator reaction to linearly enhance the SERS/RRS/FL intensity. Thus, a novel Apt turn-on tri-mode method was developed for the assay determination of ultra-trace urea with high sensitivity, good selectivity, and accuracy. In addition, trace adenosine triphosphate and estradiol can also be determined by the Apt-CDFeN catalytic analytical platform.